2010
DOI: 10.1111/j.1465-3435.2009.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Competences for Learning to Learn and Active Citizenship: different currencies or two sides of the same coin?

Abstract: In the context of the European Union Framework of Key Competences and the need to develop indicators for European Union member states to measure progress made towards the ‘knowledge economy’ and ‘greater social cohesion’ both the learning to learn and the active citizenship competences have been highlighted. However, what have yet to be discussed are the links and the overlaps between these two competences. Based on the development of research projects on these two fields, this article will compare the two set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
26

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 12 publications
2
60
0
26
Order By: Relevance
“…Digital skills and ICT competences are a pre-requisite for employment, personal fulfilment, social inclusion and active citizenship in today's rapidly-changing world (Hoskins & Crick, 2010;Ross, 2007). In a sense, education institutions are there to help their students develop competences (Halasz & Michel, 2011).…”
Section: Setting the Scene Of The Research Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital skills and ICT competences are a pre-requisite for employment, personal fulfilment, social inclusion and active citizenship in today's rapidly-changing world (Hoskins & Crick, 2010;Ross, 2007). In a sense, education institutions are there to help their students develop competences (Halasz & Michel, 2011).…”
Section: Setting the Scene Of The Research Environmentmentioning
confidence: 99%
“…Many pupils already operate offline specialised software as well as online programmes on internet (Castaño-Muñoz, Duart & Sancho-Vinuesa, 2014;Tyner, 2014). As a matter of fact, ICT has improved the ways of accessing knowledge, researching, communicating, socialising and succeeding in all levels of education (Hoskins & Crick, 2010;Smith, Higgins, Wall & Miller, 2005). Nowadays, many children and teenagers can easily access a personal computer either at home or at school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podemos dizer que as TIC são mais utilizadas como um apoio para o "trabalho diário dos professores do que como forma central do ensino pedagógico para a inovação" (Moreira [16]). Resultados no trabalho, nas relações pessoais ou na sociedade civil, não são baseadas simplesmente na acumulação de conhecimento em segunda mão armazenado como dados, mas como uma combinação desse conhecimento com habilidades, valores, atitudes, desejos e motivações e sua aplicação na configuração humana, em particular, em um determinado ponto numa trajetória no tempo, (Hoskins e Crick [17]). …”
Section: Revisão Da Literaturaunclassified
“…Wastiau et al [3] have also indicated that students have the highest frequency of digital learning technology use when taught by teachers who possess appropriate digital skills, who use the internet, including social media [9].…”
Section: Introductionmentioning
confidence: 99%